(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Succinic acid, a naturally occurring dicarboxylic acid, plays a pivotal role in cellular metabolism as an intermediate in the citric acid (Krebs) cycle. Beyond its metabolic functions, succinic acid has garnered significant attention for its wide array of therapeutic applications in modern medicine. This article delves into the pharmacological activities of succinic acid, emphasizing its anti-inflammatory, antioxidant, neuroprotective, and metabolic regulatory effects. Additionally, the article explores its emerging roles in cancer therapy, antimicrobial treatment, and its potential in combating metabolic syndrome and cardiovascular diseases.